Guidance on tasks and deliverables for different evaluation phases (Methods Lab, 2015)
This tool describes the five key phases of evaluation, from planning a nd design, to implementation and communication of results. It provides a list of the main tasks and deliverables for each phase, intended fo r use by anyone managing an impact evaluation. This tool was developed by Irene Guijt, Simon Hearn, Tiina Pasanen and Patricia Rogers for us e in Methods Lab projects. It follows to some extent the BetterEvaluat ion Rainbow Framework.